STUDI EMPIRIS LEAN MANUFACTURING DALAM MAMBANGUN DAYA SAING USAHA - Sumartono Sumartono; Petrus Megu (University of Merdeka Malang, 2016)
The purpose of this research is to analyze the effect of lean manufacturing to the business competitiveness. The research population is all craftsmen shoes and sandals in Toyomerto, Malang. By simple random sampling technique, the researcher uses 105 repondents. Primary data were analyzed by structural equation modeling (SEM). Based on the analysis, it was revealed that lean manufacturing plays a significant role to the business competitiveness. It means that, in order to build the business competitiveness of craftsmen shoes and sandals in Toyomerto, Malang Regency, they should begin to applicate the concept of lean manufacturing. That concept can make these small business entities more competitive and sustainable.